2020
DOI: 10.3390/polym12040761
|View full text |Cite
|
Sign up to set email alerts
|

Coincident Correlation between Vibrational Dynamics and Primary Relaxation of Polymers with Strong or Weak Johari-Goldstein Relaxation

Abstract: The correlation between the vibrational dynamics, as sensed by the Debye-Waller factor, and the primary relaxation in the presence of secondary Johari-Goldstein (JG) relaxation, has been investigated through molecular dynamics simulations. Two melts of polymer chains with different bond length, resulting in rather different strength of the JG relaxation are studied. We focus on the bond-orientation correlation function, exhibiting higher JG sensitivity with respect to alternatives provided by torsional autocor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…If these are not known, their estimation is a delicate (and sometimes uncertain) procedure leading to higher computational cost [13,15]. Building on previous studies carried out by Molecular Dynamics (MD) simulations, the present paper reports novel insight provided by MI-based approaches on two distinct aspects of transport and relaxation close to GT, namely dynamical heterogeneity [23,24] and its influence on secondary relaxations [25,26]. Details about the model systems and numerical methods are found elsewhere [23][24][25][26].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…If these are not known, their estimation is a delicate (and sometimes uncertain) procedure leading to higher computational cost [13,15]. Building on previous studies carried out by Molecular Dynamics (MD) simulations, the present paper reports novel insight provided by MI-based approaches on two distinct aspects of transport and relaxation close to GT, namely dynamical heterogeneity [23,24] and its influence on secondary relaxations [25,26]. Details about the model systems and numerical methods are found elsewhere [23][24][25][26].…”
Section: Introductionmentioning
confidence: 93%
“…In agreement with previous studies [53,54], we found that the chains having shorter bond length exhibits a characteristic two-step decay after a first fast decay at t ∼ 0.1, which is a signature of the presence of two distinct relaxation processes. We ascribed the faster one to the JG β relaxation and the slower one to the structural α relaxation [25,26]. Effective torsional potential resulting from the Lennard-Jones interaction between the first and the last monomers of the fragment.…”
Section: Mutual Information and Bond Reorientationmentioning
confidence: 99%
See 2 more Smart Citations
“…Leporini and co-workers, by the means of molecular dynamics simulations, studied two melts of polymer chains with different bond length, resulting in rather different strength of the Johari-Goldstein (JG) relaxation. They found that, even if changing the bond length alters both the strength and the relaxation time of the JG relaxation, it leaves unaffected the correlation between the vibrational dynamics and the primary relaxation [8].…”
mentioning
confidence: 99%